2022
DOI: 10.3390/ma15217518
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Wide-Bundle Bamboo Scrimber: A Comparison with Other Engineered Bamboo Composites

Abstract: Controlling the variability in mat structure and properties in bamboo scrimber (BS) is key to producing the product for structural applications, and wide strip scrimber (WBS) is an effective approach. In this study, the effects of scrimmed bamboo bundle morphology and product density on the properties of WBS were investigated. WBS panels were manufactured and tested using wide (200 to 250 mm) bamboo strips with different fiberization intensity. Maximum strength properties (flexural, compressive, and shear stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Even though some studies have revealed that laboratory-made composite materials seem to perform well when compared to conventional materials, the wear resistance of laboratory veneering composites is highly variable. 6,15 The fracture resistance of composite resins is increased by adding fibre reinforcement. By altering the geometry, fibre content, and fibre orientation, the properties of the composites can be altered.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have revealed that laboratory-made composite materials seem to perform well when compared to conventional materials, the wear resistance of laboratory veneering composites is highly variable. 6,15 The fracture resistance of composite resins is increased by adding fibre reinforcement. By altering the geometry, fibre content, and fibre orientation, the properties of the composites can be altered.…”
Section: Discussionmentioning
confidence: 99%
“…The BS made by hot pressing at 140°C reduces the color deepening while maintaining its high durability, and its compressive strength is higher than that of ordinary BS [48,62]. The BS made of widebundle bamboo strips (WBS) has higher utilization rate of bamboo than the traditional BS, and the cracks caused by the fiberization of wide-bundle bamboo strips form a mechanical interlocking network filled with resin after resin filling and curing, which enhances the mechanical properties of WBS, so the compressive performance of WBS is better than that of traditional BS [63].…”
Section: Compressionmentioning
confidence: 99%
“…The bending strength parallel to grain of the bending small specimens of BS without special treatment is usually between 100-150 mpa, and the failure mode is that the fiber in the tensile area is broken [17,48,58]. The bending properties MOR and MOE of BS increase with density [63].…”
Section: Bendingmentioning
confidence: 99%
“…Troughout its evolution, bamboo has fostered exchanges and infuences with other regions, particularly in Asia [3]. Found across Asia, Africa, and Central and South America [4], bamboo is prized for its sustainability [5], fexibility, and ease of fabrication. It is commonly used in crafting woven products like mats, boxes, and baskets.…”
Section: Introductionmentioning
confidence: 99%